AI Literacy Among University Students and Faculty: Similarities and Differences - Ayo, Eliza B.; Tamayo, Josan D.; Asur, Dan Erico (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study assessed AI literacy levels among 111 respondents at Centro Escolar University using a four-dimensional framework (Kong, 2024). Despite widespread AI adoption (99.1%), only 5.4% received formal training, revealing a critical educational gap. Faculty demonstrated significantly higher literacy in metacognitive (p = 0.02), affective (p < 0.01), and social dimensions (p < 0.01) compared to students. Both groups showed similar cognitive understanding and tool usage patterns. The research aligns with UN Sustainable Development Goals 4 (Quality Education) and 8 (Decent Work and Economic Growth) by identifying barriers to equitable AI education. Findings indicate urgent need for structured AI literacy programs, ethical curriculum integration, and institutional policy development to prepare students for an AI-driven workforce. This study contributes to understanding AI literacy disparities in higher education and provides evidence-based recommendations for comprehensive educational reform supporting sustainable development objectives.